Zaburzenie polegające na ograniczaniu/unikaniu przyjmowania pokarmów - rozważania w świetle wyników badań - Ziółkowska, Beata (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Advoidant/restrictive food intake disorder (ARFID) is not a new phenomenon. It has so far been recognized as possibly a non-specific eating disorder (EDNOS). However, the latest DSM-5 diagnostic classification distinguishes this syndrome from infant feeding and eating disorders (up to 6 years of age), as ARFID symptoms are also seen in older children, adolescents and adults. A short history of research on this team brings many important but insufficient to know its specific data. Due to this, it is important to undertake multidisciplinary cooperation of specialists in the field of medicine, psychology and human nutrition, both at the stage of empirical verification of the problem in the diagnostic activities and in the planning of the aid activities.